2018
DOI: 10.1111/and.13059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perfluorooctanoic acid exposure during pregnancy on the reproduction and development of male offspring mice

Abstract: This study was conducted to explore the effects of maternal exposure to perfluorooctanoic acid (PFOA) on reproduction and development of male offspring mice. Pregnant mice were given 1, 2.5 or 5 mg/kg BW PFOA daily by gavage during gestation. The results showed that the survival number of offspring mice at weaning was significantly decreased. There were no differences in the testicular index of offspring mice between PFOA exposure groups and non-PFOA group. Maternal exposure to PFOA reduced the level of testos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 43 publications
6
19
0
Order By: Relevance
“…In the present study, maternal exposure to PFOA markedly decreased placental weight and induced the interstitial edema of placental spongiotrophoblast, which probably resulted in fetal resorptions and growth retardation and compromised postnatal survival. Song et al 's studies showed that placental weight and the numbers of survival offspring mice were dramatically reduced in the PFOA-treated groups (Lau et al, 2006;Yahia et al, 2010;Song et al, 2018). This result was almost in accord with our current and previous research Chen et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, maternal exposure to PFOA markedly decreased placental weight and induced the interstitial edema of placental spongiotrophoblast, which probably resulted in fetal resorptions and growth retardation and compromised postnatal survival. Song et al 's studies showed that placental weight and the numbers of survival offspring mice were dramatically reduced in the PFOA-treated groups (Lau et al, 2006;Yahia et al, 2010;Song et al, 2018). This result was almost in accord with our current and previous research Chen et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, PFOA has attracted more attentions for reproductive and developmental toxicities (Yahia et al, 2010;Das et al, 2015;Song et al, 2018). Experiments in vivo and in vitro showed that PFOA exposure reduced testosterone production through the down-regulation of steroid hormone related synthetase (Zhao et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, PFOA-treated male mice exhibited dose-dependent reductions in testosterone and progesterone levels, reduced sperm quality, damaged seminiferous tubules and increased testicular oxidative stress at doses of 0.31 to 20 mg/kg/day [91,165]. Consistent findings were observed following in utero exposure to PFOA [166]. Male reproductive toxicity, including effects on hormone levels and fertility was observed in PFNA treated mice [98] and gestational exposure to GenX and PFHxS resulted in lower testis weight and a weak but significant association with nipple retention in males, respectively [167,168].…”
Section: Modulates Receptor-mediated Effectssupporting
confidence: 57%
“…Animal Biosassay In Vitro PFOA Association: [153]; [154]; [155]; [156]; [157] Association: reviewed in [164]; [91]; [165]; [166]; [169]; [170]; [173]; [175]; [191]; [61] No association: [174] Association: [176]; [158]; [175]; [181]; [188]; [189]; [193]; [179]; [180] No association: [182] Long-chain PFAS a PFOS Association: [154]; [155]; [156]; [157]; [160]; reviwed in [163] No Association: [153] Association: [191]; [192] Association: [177]; [175]; [181]; [188]; [189]; [193]; [179]; [180] No association: [182] PFHxS Association: [159]; reviwed in [163] No association: [...…”
Section: Epidemiologicalmentioning
confidence: 99%
“…Studies in laboratory animals have shown that PFAAs can cross the placental barrier and be transferred from mother to fetus (Das et al, ; Lai et al, ); therefore, the gestational exposure to these compounds can influence the developing fetus and produce diseases in later life. Gestational exposure to perfluorooctane sulfonate and perfluorooctanoic acid in rodents has been reported to interfere with reproductive hormones and alter testicular functions in male offspring (Lai et al, ; Song, Li, Wang, & Zhong, ). However, to the best of our knowledge, the effect of gestational exposure to PFNA on male reproductive health has not been investigated so far, despite evidence of its placental transfer from mother to the fetus.…”
Section: Introductionmentioning
confidence: 99%